Effect of Heat Treatment on the Property, Structure, and Aggregation of Skim Milk Proteins - Li, Hongbo; Zhao, Tingting; Li, Hongjuan; Yu, Jinghua (Frontiers in Nutrition, 2021)
To study the mechanism of heat-induced protein aggregates, skim milk was heated at 55, 65, 75, 85, and 95°C for 30 s. Then, the sulfhydryl content, surface hydrophobicity, and secondary structure of heat-treated skim milk were studied. Treating skim milk at different temperatures induced a decrease in sulfhydryl content (75.9% at 95°C) and an increase in surface hydrophobicity (44% at 95°C) with a disrupted secondary structure containing random coil, β-sheet, and β-turn of skim milk proteins. The change in these properties facilitated aggregate formation through disulfide bonds and hydrophobicity interaction. Microstructural observation also showed a higher degree of aggregation when skim milk was heated at 85 and 95°C. The result of two-dimensional polyacrylamide gel electrophoresis demonstrated that the aggregates consisted of a high proportion of κ-casein, β-lactoglobulin, and other whey proteins.